Oil and S&P 500 Markets: Evidence from the Nonlinear Model - Lee, Yen-Hsien; Fang, Hao (International Journal of Economics and Financial Issues, 2012)
This study begins by using a MTAR model to explore the asymmetric effects of error corrections between oil prices in the U.S.A and S&P 500 prices under different regimes. After confirming the lead/lag relationship between the S&P 500 and oil prices, we employ a STECM to analyze the short-run return dynamics when there are deviations from the equilibrium between the two variables. Our empirical evidence shows that an asymmetric co-integration relationship exists between the S&P 500 and oil prices. In addition, the results of the Granger causality test based on the TECM document the unidirectional relationship from the oil price to the S&P 500 price. Moreover, the short-run adjustments of the mean reversion to equilibrium follow the LSTECM. The contribution of this study might be in that the LSTECM-GARCH model is well suited to describing the short-run return dynamics of the disequilibrium between the oil prices and S&P 500 prices in the U.S.A. Keywords: Threshold Co-integration Test; Threshold Error-Correction Model; Stock Market; Oil Market; STECM-GARCH Model JEL Classifications: C13; C22; C32; G18; G10; Q42